(untitled) (PANGEEA, 2025)
The church and environment protection. Article provides a reviw of the relationship between church and environmental protection. For a long period of time church was not involved enough in environmental education. In the last years churches of different denominations take clear positions in terms of environmental protection. What was been done is more of a general nature. Therefore tendency in the present is to identify possibilities for action by the churches in their relationship with the environment. We believe that in the future is needed a great involvement of churches and also the churches should reconsider their relations with environmental authorities.